Sushi or fish fingers? Seafood diversity, collapsing fish stocks, and multi-species fishery management - Martin F. Quaas; Till Requate (Kiel University, Department of Economics, 2012)
We present a model of a multi-species fishery and show that (i) consumer preferences for seafood diversity may trigger a sequential collapse of fish stocks under open-access fishery, (ii) the stronger the preferences are for diversity the higher is the need for coordinated multi-species regulation, (iii) second-best optimal management of only one (or a few) species is less strict than socially optimal management of the same species. Finally, (iv) myopic regulation of one species, ignoring spill-overs to other species, may cause depletion of other stocks that would not be depleted under open access.
Keywords: Q22; Q57; Q21; 330; marine biodiversity; fishery economics; product differentiation; Fischereiressourcen; Meeresprodukt; Produktdifferenzierung; Biodiversität; Erneuerbare Ressourcen; Theorie